Triiodothyroacetic Acid Cross-Reacts With Measurement of Triiodothyronine (T3) on Various Immunoassay Platforms. Issue 2 (20th September 2021) - Chan, Siaw Li; Refetoff, Samuel; Babic, Nikolina; Jin, Ming; Garg, Uttam; Yeo, Kiang-Teck J
Abstract: Objectives: Thyroid hormone analog 3, 5, 3'-triiodothyroacetic acid (TRIAC) is effective in reducing the hypermetabolism in monocarboxylate transporter 8 (MCT8)–deficient individuals. Because of the structural similarity between TRIAC and 3, 3', 5'-triiodothyronine (T3 ), we sought to investigate the degree of cross-reactivity of TRIAC with various commercially available total and free T3 assays. Methods: Varying concentrations (50-1, 000 ng/dL) of TRIAC (Sigma Aldrich) were added to pooled serum and assayed for total T3 (TT3 ) and free T3 (FT3 ) on the following platforms: e602 (Roche Diagnostics), Architect (Abbott Diagnostics), Centaur (Siemens Healthcare Diagnostics), IMMULITE (Siemens Healthcare Diagnostics), DxI (Beckman Coulter), and Vitros (Ortho Clinical Diagnostics). TT3 competition assay with TRIAC was performed by adding increasing amounts of T3 to pooled serum samples that contained a constant concentration of TRIAC (250 ng/dL). Results: Significant overestimation of TT3 and FT3 assays were observed across all platforms corresponding to increasing concentrations of TRIAC. The TRIAC effect at 250 ng/dL showed a constant interference of approximately 190 ng/dL TT3 . Conclusions: All commercial TT3 and FT3 assays tested in this work cross-react significantly with TRIAC. Therefore, patients undergoing TRIAC therapy should have T3 hormone response monitored using alternative nonimmunoassay-based methods to avoid misinterpretation of thyroid function profiles.